AUTOMATIC CONSTRUCTION METHODS OF ABSTRACTS ON THE BASIS OF THE TEXTS FREQUENCY ANALYSIS - F. I. Tretyakov; L. V. Serebryanaya (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Algorithms of author's abstracts construction on the basis of the texts frequency analysis are considered. Their comparative analysis of algorithms is made, and also ways of quality improvement of the author's abstract are offered. The algorithm of drawing up of the summary abstract is realized. The program module for automatic construction of abstracts on the basis of the developed methods is created.